SOURCE OF KNOWLEDGE THROUGH AXIOLOGY PERSPECTIVE - Nurhayati, Nurhayati; Nasution, Ibrahim Haidar; Siregar, Rafiqah Yusna (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2023)
ABSTRACTThe research aims to discuss the axiological values and sources of knowledge for humans. This research uses the Semut Sumut non-formal education organization as a case study. This article employs a qualitative interpretive approach by conducting library research, specifically by looking at reading materials related to the studies presented and using document analyses of earlier research findings associated with the philosophy of science. Books rading, scientific journals on Google Scholar, and digital libraries were combed through to acquire the data. Results of this study show that axiological values as a source of knowledge can be reflected in social movements by providing non-formal education platforms for children who have dropped out of school or even have no opportunity at all to go to school. The axiological value of social movements contains elements of being functional, robust, valid or strong which means the quality of something that makes it liked, appreciated and appreciated by other parties. In addition, two supporting elements in non-formal learning materials further strengthen the axiological perspective as a source of knowledge, namely ethics and aesthetics. Keywords: Axiology, Knowledge, Semut Sumut.